Understanding Leukemogenesis: Challenges and Advancements in Diagnostic Approaches - Brian Ndubi; Ajit Pal Singh (International Journal of Biomedical Innovations and Engineering, 2025)
Leukaemia development, or leukemogenesis, is a multifactorial process driven by a complex interplay of environmental, genetic, and epigenetic factors. Despite substantial advancements in technology and medicine, which have enhanced our understanding of the contributing factors, early and accurate diagnosis remains a major challenge due to the overlapping clinical features shared by the various leukaemia subtypes. This study explores the molecular and cellular mechanisms underlying leukemogenesis, while also addressing the difficulties in distinguishing between leukaemia subtypes. Furthermore, it reviews the current diagnostic procedures and evaluates the role of emerging technologies and tools that hold promise for improving diagnostic precision. The inherent variability of leukaemia, combined with its numerous subtypes, makes accurate diagnosis exceedingly difficult, even considering recent strides in elucidating the molecular pathways involved in leukemogenesis. The presence of measurable residual disease (MRD) further complicates the assessment of treatment response and the prediction of relapse. Additionally, substantial inter- and intratumorally heterogeneity adds layers of complexity in identifying consistent diagnostic biomarkers. One of the most significant challenges lies in the identification of reliable biomarkers capable of distinguishing between patients who respond to therapy and those who do not. Recent advances in next-generation sequencing (NGS) and genomic profiling have greatly expanded our knowledge of the genetic underpinnings of leukaemia, yet translating these findings into clinical practice remains problematic. The challenge persists in applying these discoveries effectively within the diagnostic and therapeutic landscape. This abstract underscore the urgent need for continued research aimed at developing more precise, personalized diagnostic tools. Such advancements are critical not only to enhance early diagnosis but also to improve treatment outcomes and enable more effective management of leukaemia patients.
Keywords: Biomarkers; Inherent; Leukaemia; diagnosis; treatment